NARASI ILUSTRASI KONTEMPORER : SEBUAH PENDEKATAN EKSPERIMEN - Eston Kamelang Mauleti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2023)
In accordance with one of the elements of the Tri Dharma of Higher Education, Community Service was carried out through Contemporary Illustration Art Education training at PKBM Negeri 26 Bintaro, South Jakarta. The purpose of this training is to provide knowledge and briefing to students about the development of the world of illustration which is currently growing rapidly, especially in Indonesia. The basis of illustration is drawing, in this training students are given teaching and guidance on drawing illustrations through a contemporary illustration approach. The meaning of the word contemporary means